Body image terhadap self-confidence pada remaja putri yang menikah - Gumi Langerya Rizal; Sherly Agustin (Cognicia, 2022)
This research is based ons a phenomenon related to married young women who experience changes in body image in Air Hangat Barat. Changes in the body image of married young women if they cannot accept it will have a negative impact, especially lack of confidence. This study aims to see the contribution of body image to self confidence in married young women. This study uses a correlational quantitative design. Subjects were taken using a purposive sampling technique with criteria for age at marriage 17-22 years, current age 17-22 years years in Air Hangat Barat. This study obtained 60 respondents. Data collection using a body image and self-confidence scale by distributing questionnaires then analyzed using a simple linear regression formula. The results showed that the value of r = 39.349 (p (p <0.05) means that there is a positive relationship between body image and self-confidence. The more positive the body image, the more positive the self-confidence and vice versa, the more negative the body image, the more negative the self-confidence.  Keywords: body image, self confidence, young women married